Correlation between the inframammary fold and sixth rib: Application to breast reconstruction. Issue 2 (23rd May 2019) - Oh, Sangho; Kim, Dongseok; Kim, Junhyung; Choi, Jaehoon; Jeong, Woonhyeok; Han, Kihwan; Son, Daegu
Abstract : The inframammary fold (IMF) is an essential aesthetic element that influences the outcome of breast surgery. In this study, we introduced a new method for finding the IMF based on retrospective analysis of chest computed tomography (CT) scans of women's breasts. Sagittal sections of 80 female chest CTs were analyzed. Sagittal sections of 80 female chest CTs were analyzed by a single plastic surgeon. The distances between the fifth, sixth, and seventh ribs and the IMF were measured using Photoshop, and the location of the IMF was statistically analyzed according to age and height using paired t tests and Pearson's correlation test. As determined by our new method, the average distance between the IMF and the sixth rib was 5.33 mm, which was less than that between the IMF and any other rib. The IMF was closest to the sixth rib in all age groups ( P  < 0.001), and all IMFs were located between 39.5 mm superior and 24 mm inferior to the sixth rib. The sixth rib, one of the most visible reference structures in women's surface anatomy, is the "sentinel rib" for the IMF and the most predictive indicator of the location of the IMF. Knowing the original anatomic location of the IMF will enable better outcomes during breast surgery. Clin. Anat. 33:165–172, 2020. © 2019 Wiley Periodicals, Inc.